Evaluation of the prospects of hedging Botswana's maize prices against the Johannesburg Stock Exchange commodity market derivatives - Owusu-Sekyere, Enoch (University of Pretoria, 2022)
Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2022